PENGARUH GADGET TERHADAP PERKEMBANGAN KOGNITIF ANAK PADA USIA 5 SAMPAI 14 TAHUN - Jumianti Anton Lapu' (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
The use of gadgets among children aged 5 to 14 has increased significantly alongside the advancement of digital technology. This phenomenon has a complex impact on children’s cognitive development, particularly in areas of thinking, concept formation, and logical abilities. This study aims to analyze in depth the influence of gadgets on children’s cognitive development using Jean Piaget’s cognitive development theory as the conceptual framework. The research method employed is qualitative, based on a literature review, examining various literatures, scientific articles, and relevant previous studies. The findings indicate that gadgets can provide benefits in enhancing symbolic learning, creativity, and problem-solving skills in children. Children can use digital media to explore new concepts visually and interactively. However, excessive use of gadgets may reduce social interactions, hands-on play experiences, and physical activities that are essential for cognitive and emotional development. These negative impacts can affect children’s critical thinking, communication skills, and the development of empathy. Therefore, this study emphasizes the importance of guidance and supervision from parents and educators to ensure that children utilize technology optimally. Managing usage time, selecting educational content, and combining digital activities with real social interactions are essential strategies to support balanced cognitive development in children.